HUMAN PSYCHOLOGY IN SHAKESPEARE’S WORKS - Sultonova Umida Rashid qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The exploration of human psychology in literature provides deep insights into the complexities of emotions, thoughts, and behaviors. William Shakespeare, one of the greatest playwrights in English literature, masterfully depicted the intricacies of the human mind through his diverse characters and dramatic plots. His works are not merely stories of ambition, love, betrayal, or power but profound psychological studies of human nature. Shakespeare’s ability to capture the depth of emotions such as jealousy, guilt, ambition, and existential doubt has made his plays timeless and universally relevant. This paper aims to explore how Shakespeare portrays human psychology in his works, focusing on the internal conflicts, moral dilemmas, and emotional struggles of his characters. By analyzing key plays such as Hamlet, Macbeth, Othello, and King Lear, this study will highlight how Shakespeare’s characters reflect the complexities of the human psyche and how his insights into human behavior continue to resonate with modern audiences.